2011
DOI: 10.1142/s0192415x11008968
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Qigong Practice and Upper Respiratory Illness in Elite Swimmers

Abstract: Upper respiratory tract infections (URIs) are a common complaint in competitive swimmers and can adversely affect performance. No intervention has yet been shown to reduce URI incidence in intensively trained athletes. The University of Virginia varsity swim team received three weeks of training in qigong for the purpose of reducing stress and improving health. Our primary objective was to assess the relationship between qigong practice and symptoms of URI during a time when swimmers would be at high URI risk.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Long term practice of qigong exercise may help to prevent illness or heal the body from diseases. Although the underlying mechanism for its health benefits is not yet well understood, there are increased reports of its effects on health (Ng and Tsang, 2009;Vincent et al, 2010;Wright et al, 2011). Basically, there are two categories of qigong: internal qigong and external qigong.…”
Section: Introductionmentioning
confidence: 99%
“…Long term practice of qigong exercise may help to prevent illness or heal the body from diseases. Although the underlying mechanism for its health benefits is not yet well understood, there are increased reports of its effects on health (Ng and Tsang, 2009;Vincent et al, 2010;Wright et al, 2011). Basically, there are two categories of qigong: internal qigong and external qigong.…”
Section: Introductionmentioning
confidence: 99%
“…The estimates of the number of subjects needed to test our hypothesis were based on the experience about RE training in UVa swimmers [ 6 ] and a separate volunteer study conducted with the CT on volunteers previously taught RE (unpublished observations). From the first study the impression was that swimmers are well motivated to learn this meditation technique and that a majority of them continue to practice during the sports season.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have reported URI incidences of 42–45% during training periods ranging from 4 to 12 weeks [ 1 3 ] while other studies showed an 8-week incidence of respiratory illness of 84% [ 4 ]. These ill effects can be thwarted by the practice of reflective exercise (RE, a westernized form of Qigong) [ 5 ] shown by a reduction of URIs in varsity swimmers who maintained practice [ 6 ]. The enhanced athletic performance associated with combinations of breathing, relaxation, meditation, guided imagery, and slow movement exercises supports the notion that these practices can enhance immunity [ 7 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…MQ is practiced by all ages, ethnicities, and genders. Several studies have focused on older adults who routinely practice MQ Stenlund, Lindström, Granlund, & Burell, 2005) as well as young, college-aged athletes (Wright, Innes, Alton, Bovbjerg, & Owens, 2011).…”
Section: Benefits Of Qigongmentioning
confidence: 99%